A Comparison of Greenhouse Gas Emissions from Uruguayan and New Zealand Beef Systems - Becoña López, Gonzalo; Ledgard, Stewart; Wedderburn, Elizabeth (Agrociencia Uruguay, 2013)
In order to reduce greenhouse gas (GHG) emissions from beef production Uruguayan and New Zealand systems have a significant role to play. Despite the differences, both are exposed to the same threats, i.e. more profitable alternative systems competing for the land, with enhanced production through intensification being a common response, and increasing pressure on the environment. This issue has attracted attention around the world concerning climate change and GHG emissions associated with animal production systems. The comparison using a whole-farm model (OVERSEER®), shows clear differences in GHG emissions, with higher emissions (in carbon dioxide equivalents, CO2 eq) per kilogram of beef on Uruguayan farms (18.4-21.0 kg CO2 eq/beef) compared with New Zealand farms (8-10 kg CO2 eq/beef) as a result of lower production efficiency. However, the emissions per hectare were higher on intensive New Zealand farms (3013-6683 kg CO2 eq/ha/year) than on Uruguayan farms (1895-2226 kg CO2 eq/ha/year) due to high stocking rates and increased inputs. Sensitivity analysis revealed a large effect of methodology and the benefit of using tier 2 factors that account for differences in animal productivity and feed quality. Nitrous oxide emissions factors for animal excreta determined in New Zealand are half of the default IPCC factors, while activity factors for indirect nitrous oxide emissions from excreta-ammonia and N leaching are 50% and 23% respectively. Increased feed conversion efficiency in the more intensive systems was associated with lower GHG intensity but farm systems also need to account for other environmental factors that are more important on a regional or catchment basis.